Giving effect to EEA law : examining and rethinking the role and relationship between the EFTA Court and the Icelandic National Courts in the EEA legal order - HANNESSON, Ólafur Ísberg (European University Institute, 2013)
Defence date: 21 January 2013 Examining Board: Professor Ernst-Ulrich Petersmann, European University Institute (Supervisor); Professor M. Elvira Mendez-Pinedo, University of Iceland (external co-supervisor); Professor Miguel Poiares Maduro, European University Institute; Judge Páll Hreinsson, EFTA Court. PDF of thesis uploaded from the Library digital archive of EUI PhD theses Doctrines developed by the EFTA Court have placed considerable demands on the various national courts in the EFTA States. The Court now considers the EEA Agreement to form an "international treaty sui generis which contains a distinct legal order of its own." This thesis will study the interaction between the EFTA Court and Icelandic courts. The basis of this research rests on two levels. At the EEA level, it is the ECJ and the EFTA Court that form the basis of the study. At the national level, the thesis studies Icelandic Supreme Court and district court decisions. I will approach the question of the impact of EEA law on Icelandic domestic law from two dimensions: substantive and procedural. In substantive terms, the study examines fundamental European judgemade principles, as well as the impact these doctrines have had on Icelandic law. This will indicate how Icelandic courts deal with potential conflicts of law between EEA and Icelandic law, and how they respond to EFTA Court decisions and EEA principles. This part examines many fundamental concepts of EEA law, but the subject mainly raises questions concerning four specific concepts and the reaction of the Icelandic system to them. These are: first, the question of direct effect in EEA law second, the obligation of national courts to interpret national law in the light of EEA law third, the primacy of implemented EEA law and fourth, the principle of State liability. These legal concepts have all been seen as posing specific challenges to Icelandic courts. In its second stage, the thesis will, in procedural terms, study the relationship between the EFTA Court and the Icelandic ...